Evaluation of anti-tuberculosis induced adverse reactions in hospitalized patients - Gholami K; Kamali E; Hajiabdolbagh M; Shalviri G (Centro de Investigaciones y Publicaciones Farmaceuticas, 2006)
Background: Tuberculosis has been one of the common diseases of human communities. Besides of disease-related complications, there are serious adverse reactions due to Anti-tuberculosis (Anti-TB) drug therapy. Objectives: To assess the rate of Adverse Drug Reactions (ADRs) induced by Anti-TB drugs in the infectious disease department for a period of one year. To detect serious and preventable recognized ADRs. Methods: All patients admitted to the infectious disease department at Imam tertiary teaching hospital in Iran who received Anti-TB drugs from July 2001 to July 2002 entered the study. These patients were monitored for ADRs during hospital stay. The ADRs were then classified based on patients and reactions factors. The causality and severity of the reactions were determined using Naranjo algorithm and Hartwig questionnaire, respectively. Results: During the study period, 83 patients received Anti-TB drugs; of them 44 developed at least one ADR. Total number of 81 ADRs was detected in this study. ADRs were recognized as the major cause of hospital admission in 11 (13.3%) patients. The most frequent system-organ class affected by ADRs was Liver and biliary system (37%). Hepatitis was observed in 21 (25.3%) patients leading to death in two patients. Conclusion: Anti-TB drugs could cause significant adverse effects both in quantity and severity leading to hospitalization, prolonged hospital stay and even death. More attention is needed to prevent these reactions.